2022
DOI: 10.3389/fpls.2022.1025122
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining reveals abiotic stress resistance genes in plant genomes acquired from microbes via HGT

Abstract: Colonization by beneficial microbes can enhance plant tolerance to abiotic stresses. However, there are still many unknown fields regarding the beneficial plant-microbe interactions. In this study, we have assessed the amount or impact of horizontal gene transfer (HGT)-derived genes in plants that have potentials to confer abiotic stress resistance. We have identified a total of 235 gene entries in fourteen high-quality plant genomes belonging to phyla Chlorophyta and Streptophyta that confer resistance agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 79 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have suggested that Candida parapsilosis , Schizosaccharomyces pombe , and Nesidiocoris tenuis all acquired PhzF homologs from bacteria via HGT (Fitzpatrick et al ., 2008; Ferguson et al ., 2021). HGT is a natural biological process that facilitates the exchange of genetic material between distantly related lineages, which allows organisms to acquire novel traits and exploit unexplored resources (Bublitz et al ., 2019; Li et al ., 2022). For instance, Thinopyrum elongatum gained Fusarium head blight resistance gene Fhb7 through HGT from an endophytic Epichloë species, which confers broad resistance to Fusarium species by detoxifying trichothecenes (Wang et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that Candida parapsilosis , Schizosaccharomyces pombe , and Nesidiocoris tenuis all acquired PhzF homologs from bacteria via HGT (Fitzpatrick et al ., 2008; Ferguson et al ., 2021). HGT is a natural biological process that facilitates the exchange of genetic material between distantly related lineages, which allows organisms to acquire novel traits and exploit unexplored resources (Bublitz et al ., 2019; Li et al ., 2022). For instance, Thinopyrum elongatum gained Fusarium head blight resistance gene Fhb7 through HGT from an endophytic Epichloë species, which confers broad resistance to Fusarium species by detoxifying trichothecenes (Wang et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The top 200 database hits ( E ‐value < E‐70, bit‐score > 230) were downloaded by B lastp search. The phylogeny construction was conducted using the neighbor‐joining method and 1000 bootstrap replicates (with bootstrap values in black showing on respective branches; Li et al ., 2022). The resulting tree was midpoint rooted, and the tree layout was further edited using M ega 5.2 (Xia et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In the HS treatments of Plagia, only chlorophyte-related OTUs seemed to withstand the scrubber effluent pressure, because their richness and relative abundances remained unchanged, in agreement with microscopy observations (Genitsaris et al, 2023). Genome mining has identified numerous gene entries coding resistance to several sources of pollution in chlorophyte genomes (Li et al, 2022).…”
Section: Metabarcodingmentioning
confidence: 99%
“…Horizontal gene transfer (HGT), or the interchange of genetic material across phylogenetic clades, is thought to be an efficient strategy for dispersing reproductive fitness for prokaryotic and eukaryotic cells (Huang, 2013;Daubin and Szöllősi, 2016;Li et al, 2022). Employing transmitting mobile genetic elements (MGEs) like plasmids, viruses, transposons, and gene transfer agents (GTA, tailed phage-like entities capable of packing and transferring random pieces of the host genome) as well as by direct absorption and assimilation of naked DNA by homologous or unauthorized recombination, new genes are transferred through HGT (Thomas and Nielsen, 2005;Lang and Beatty, 2007).…”
Section: Introductionmentioning
confidence: 99%